Impact of depth filtration on disulfide bond reduction during downstream processing of monoclonal antibodies from CHO cell cultures. Issue 7 (4th April 2019) - O'Mara, Brian; Gao, Zhong‐Hua; Kuruganti, Manju; Mallett, Robert; Nayar, Gautam; Smith, Laura; Meyer, Jeffrey D.; Therriault, Jon; Miller, Cameron; Cisney, John; Fann, John
Abstract: Monoclonal antibody interchain disulfide bond reduction was observed in a Chinese Hamster Ovary manufacturing process that used single‐use technologies. A similar reduction has been reported for processes that involved high mechanical shear recovery unit operations, such as continuous flow centrifugation and when the clarified harvest was stored under low dissolved oxygen (DO) conditions (Trexler‐Schmidt et al., 2010. Biotechnology and Bioengineering, 106 (3), 452–461). The work described here identifies disposable depth filtration used during cell culture harvest operations as a shear‐inducing unit operation causing cell lysis. As a result, reduction of antibody interchain disulfide bonds was observed through the same mechanisms described for continuous flow centrifugation. Small‐scale depth‐filtration models were developed, and the differential pressure (Δ P ) of the primary depth filter was identified as the key factor contributing to cell lysis. Strong correlations of Δ P and cell lysis were generated by measuring the levels of lactate dehydrogenase and thiol in the filtered harvest material. A simple risk mitigation strategy was implemented during manufacturing by providing an air overlay to the headspace of a single‐use storage bag to maintain sufficient DO in the clarified harvest. In addition, enzymatic characterization studies determined that thioredoxin reductase and glucose‐6‐phosphate dehydrogenase are critical enzymes involved in antibody reduction in a nicotinamide adenine dinucleotide phosphate (NADP + )/NADPH‐dependent manner. Abstract : Depth filtration recovery of CHO cell culture was identified as a shear inducing unit operation responsible for cell lysis and release of endogenous redox enzymes, substrates, and cofactors leading to antibody reduction. The authors identified critical differential pressure (ΔP) limits of the primary depth filter required to minimize cell lysis and corresponding antibody reduction and found LDH and free thiol levels correlated to ΔP. Additionally, an active air overlay in the clarified harvest vessel during storage successfully prevented antibody reduction.